A Putative C2H2 Transcription Factor CgTF6, Controlled by CgTF1, Negatively Regulates Chaetoglobosin A Biosynthesis in Chaetomium globosum - Yan, Yu; Xiang, Biyun; Xie, Qiaohong; Lin, Yamin; Shen, Guangya; Hao, Xiaoran; Zhu, Xudong (Frontiers in Fungal Biology, 2021)
Gα signaling pathway as well as the global regulator LaeA were demonstrated to positively regulate the biosynthesis of chaetoglobosin A (ChA), a promising biotic pesticide produced by Chaetomium globosum. Recently, the regulatory function of Zn2Cys6 binuclear finger transcription factor CgcheR that lies within the ChA biosynthesis gene cluster has been confirmed. However, CgcheR was not merely a pathway specific regulator. In this study, we showed that the homologues gene of CgcheR (designated as Cgtf1) regulate ChA biosynthesis and sporulation in C. globosum NK102. More importantly, RNA-seq profiling demonstrated that 1388 genes were significant differentially expressed as Cgtf1 deleted. Among them, a putative C2H2 transcription factor, named Cgtf6, showed a highest coefficient of variation in zinc-binding proteins encoding genes as Cgtf1 deleted. qRT-PCR analysis confirmed that expression of Cgtf6 was significantly reduced in CgTF1 null mutants. Whereas, deletion of Cgtf6 resulted in the transcriptional activation and consequent increase in the expression of ChA biosynthesis gene cluster and ChA production in C. globosum. These data suggested that CgTF6 probably acted as an end product feedback effector, and interacted with CgTF1 to maintain a tolerable concentration of ChA for cell survival.